THE ROLE OF EMPLOYEE ACHIEVEMENTS: COMPENSATION AND MOTIVATION - Hanifah Jasmin; Zulaspan Tupti (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
This study aims to determine the effect of skills and motivation on work performance at PT. State Savings Bank (Persero) Tbk Medan Branch. This study uses an association approach. The population of this survey includes all employees of PT. State Savings Bank (Persero) Tbk Medan with a sample of 95 people. Based on the test results, it is possible to get the effect of competence on the work carried out. The results of the t-test 2,444 > ttable 1,661, then H0 is rejected, this indicates that there is a compensation effect on work performance. Based on the partial test results, motivation has an effect on work performance, obtained tcount 2.451 > ttable 1.661. The results of the f test obtained the calculated F value of 13.922 and Ftable 3, 094 which shows that H0 is rejected means that compensation (X1) and motivation (X2) together have an effect on work performance (Y) with a significant 0.000 <0.05. R Square value of 0.232 > or 23.2% shows that 23.2 work performance variables (Y) are affected by compensation (X1) and motivation (X2), the remaining 76.8% is explained by other variables that are not known in this study. Due to the small population size, the entire population is         add sample.